Expression of ERCC1, p53, and Class III β-Tubulin Do Not Reveal Chemoresistance in Endometrial Cancer: Results From an Immunohistochemical Study. Issue 6 (1st August 2011) - Vandenput, Ingrid; Capoen, An; Coenegrachts, Lieve; Verbist, Godelieve; Moerman, Philippe; Vergote, Ignace; Amant, Frédéric
Abstract : Background: In non-small cell lung cancer, expression of excision repair cross-complementation group 1 (ERCC1) and p53 correlates with platinum resistance and class III β-tubulin with resistance to taxanes. The potential to personalize treatment in endometrial cancer remains uninvestigated. Methods: Patients received platinum-based chemotherapy, with or without paclitaxel. Patients were divided into 2 groups: group A (n = 33) consisted of patients with early-stage endometrial cancer treated with adjuvant chemotherapy. Group B (n = 116) included cases with primary advanced or recurrent disease. Immunohistochemistry was performed to analyze the expression of ERCC1 and p53, for all cases, and class III β-tubulin for cases treated with paclitaxel. The findings were correlated with response according to Response Criteria in Solid Tumors; recurrence-free, disease-specific survival; and established prognostic markers. Results: The mean age of 149 patients was 64 years (range, 31-84 years). Distribution of histopathologic subtypes was as follows: 44 endometrioid (30%), 92 serous/clear cell (62%), and 13 carcinosarcomas (8%). In group A, 11 (33%) and 19 patients (58%) showed expression for ERCC1 and p53, respectively. Seven (78%) of nine patients receiving paclitaxel were positive for class III β-tubulin. There was no correlation between expression of ERCC1, p53, or class III β-tubulin and recurrence or survival. In group B, 25 (22%) and 61 patients (64%) were positive for ERCC1 and p53, respectively. Fifty-two (74%) of seventy patients receiving paclitaxel were positive for class III β-tubulin. Only p53 expression correlated with survival ( P = 0.01). Conclusions: In contrast to theoretical assumptions, the current study did not reveal evidence that the expression of ERCC1 and class III β-tubulin predicts response to cytotoxic treatment and patient outcome in endometrial cancer.